PENGARUH KEMAMPUAN IBU HAMIL DALAM MELAKUKAN DETEKSI DINI RISIKO PREEKLAMSIA TERHADAP PARITAS, PENGETAHUAN DAN KETERPAPARAN INFORMASI - Rr. Galuh Ajeng Indu Dewi (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2017)
Health conditions, mental status and Life & Style can be lead to complications on Pregnancy can be causing death of mother and fetus (Depkes RI, 2014). The main factor that cause maternal death are postpartum bleeding / HPP (28%), preeclampsia (24%) and infection (11%) (Indonesia Health Profile, 2007). Those factors that cause maternal death actually could be prevented by pregnancy and early detection of the risk of pregnancy check up. The type of this research is analitic observational by using cross sectional design. The population is consist of 171 pregnant mother. The sample used are amount of 62 pregnant mothers. The sample used is probability sampling with stratified random sampling technique. Data collection using primary data with questionnaire instrument through interview. Furthermore, the data would be analyzed with simple logistic regression analysis and multiple logistic regression analysis with the level of meaning 5% (α = 0,05). Based on the results of multiple logistic regression analysis in Sawahan show disclosure information variable of danger signs with significancy Exp value (B) 5,657 are significant variables and variable of paritas with significancy Exp value (B) 9,060 are significant variables. Sawahan Public Health Center is the Public Health Center which has high of Maternal Mortality Rate. Puskesmas Sawahan must have information forum. So that, pregnant mother and the other patient or patient’s family should get more information about the danger signs of pregnancy, especially preeclampsia.